Management of chemotherapy-related symptoms in children and adolescents: family caregivers' perspectives - Fernanda Machado Silva-Rodrigues; Milena de Lucca; Ana Carolina Andrade Biaggi Leite; Willyane de Andrade Alvarenga; Michele Darezzo Rodrigues Nunes; Lucila Castanheira Nascimento (SciELO, 2021)
ABSTRACT Objective: To describe the chemotherapy-associated symptoms and the strategies used for their management from the perspective of pediatric cancer patients' family caregivers. Methods: This is a descriptive study with qualitative data analysis. Data collection took place in a pediatric hospital, from December 2017 to December 2018, with family caregivers of pediatric patients undergoing chemotherapy. Semi-structured interviews, subjected to inductive content analysis, were carried out. Concepts from the Symptom Management Theory were used to discuss the results. Results: Eighteen family caregivers participated. The participants mentioned: physical symptoms, especially weakness, alopecia, low immunity, pain, mucositis, constipation, nausea, and vomiting; emotional or psychosocial symptoms such as sadness and mood changes; and constitutional symptoms such as loss of appetite and fever. Pharmacological and non-pharmacological measures were mentioned in the management of symptoms and adverse effects. Conclusion: Participants demonstrated skills to identify and manage symptoms of chemotherapy. Knowing the experience of these families can help nurses in planning care and interventions to minimize these events.